To Grow Strategy - Modak (2025)
Modak has made financial education accessible for teenagers aged 13 to 17 but has identified a significant gap in reaching children under 13. This younger audience requires a different approach, tailored to their interests, cognitive abilities, and ways of learning. This design project introduces the To Grow strategy, a capsule made up of three key touchpoints (MiniMentor, What’s the Price?, and MoRecap) aimed at fostering exploration, reflection, and recognition in early financial learning. Through this strategy, Modak is empowered to expand its impact by nurturing a positive relationship with money from an early age, built on emotional and everyday connections between children and their parents. To inform the project, interviews and surveys were conducted with both parents and children to better understand their needs, motivations, and expectations regarding financial learning. The findings revealed a crucial emotional bond between parents and children that can be leveraged to strengthen financial habits through real life experiences. Additionally, it was found that children are more motivated to learn when doing so in playful environments and alongside their caregivers. As a result, an integrated strategy was developed to promote motivation, joint participation, and experiential financial learning in childhood. This project encourages Modak to pave the way for children to take risks, explore, make mistakes, learn, and build a healthy and confident relationship with money from a young age.